Biochar for sustainable additive manufacturing: Thermal, mechanical, electrical, and rheological responses of polypropylene-biochar composites - Petousis, Markos; Maravelakis, Emmanuel; Kalderis, Dimitrios; Saltas, Vassilios; Mountakis, Nikolaos; Spiridaki, Mariza; Bolanakis, Nikolaos; Argyros, Apostolos; Papadakis, Vassilis; Michailidis, Nikolaos; Vidakis, Nectarios (Biomass & bioenergy, 2024)
The utilization of eco-friendly reinforcing materials and the fabrication of sustainable composites with enhanced mechanical and electrical properties are a subject of great scientific interest. Such research is aiming to be applied in a variety of industrial applications. In this study, polypropylene (PP) was used as a matrix material and combined with biochar (BC) as a filler at different loadings (2.0, 4.0, 6.0, 8.0, and 10.0 wt %) to produce reinforced composites. Biochar was produced from olive tree prunings. Additively manufactured specimens underwent a variety of tests (fourteen in total) regarding their thermal, structural, mechanical, morphological, and electrical properties. The mechanical properties of the PP were improved by the addition of 4.0 wt % biochar, as the tensile strength and modulus of elasticity, presented a 28.4 % and 24.3 % increase compared to that of pure PP. Overall, the 6 wt % was the optimum loading considering all the tests conducted. The thermal stability of the PP/BC composites was significantly improved compared to that of pure PP. At a filler loading of 8.0 wt %, the dc-conductivity of PP/biochar composite increased by more than 9 orders of magnitude, suggesting the existence of a percolation threshold, above which the polymer composite switches from insulating behavior to a conductive state. Overall, biochar addition had a positive impact on all measured quantities and proved to be an eco-friendly material suitable for use in various applications of additive manufacturing (AM). [Display omitted] •Reinforcement of MEX 3D printed parts with the eco-friendly biochar, derived from olive trees.•The popular Polypropylene was the matrix material.•Eco-friendly composites achieved high-performance mechanical properties.•28.4 % and 24.3 % 9 improvement in tensile strength and modulus vs. pure PP for the 4.0 wt. % biochar loaded composite.•Electric conductivity was induced to the composites by the biochar filler (increased by 9 order of magnitude).